Prospective evaluation of pericardial catheter placement versus needle pericardiocentesis in the management of canine pericardial effusion. Issue 1 (4th December 2020) - Cook, Simon; Cortellini, Stefano; Humm, Karen
Abstract: Objective: To compare the safety and efficacy of pericardial catheter placement with needle pericardiocentesis in dogs with pericardial effusion (PE) Design: Prospective, randomized clinical trial. Setting: University teaching hospital. Animals: Thirty client‐owned dogs requiring pericardiocentesis between January 2017 and August 2019. Interventions: Dogs were randomized to undergo PE drainage via indwelling pericardial catheter placement (catheter group) followed by elective drainage every 4–6 hours or needle pericardiocentesis (needle group) repeated as necessary. Measurements and main results: Fifteen dogs were allocated to the catheter group and 15 to the needle group. Data collected included signalment, cause of effusion, occurrence of arrhythmias pre‐, during, and post‐pericardiocentesis, procedural length, and details of repeated drainages. There was no significant difference between mean procedural times for pericardial catheter placement (17.7 min [±11.8]) and needle pericardiocentesis (12.1 min [±8.6]) ( P = 0.192) or the rate of new arrhythmias in the catheter (36%) and needle (64%) groups ( P = 0.24). Pericardial catheters were kept in situ for a median of 21 hours (range, 14–85). Three of 15 (20%) dogs in the needle group required repeated pericardiocentesis within 24 hours of initial pericardiocentesis. Pericardial catheters enabled repeated large volume PE drainage in 4 cases (median, 10.6 mL/kg; range, 8‐5–10.6). Conclusions: Pericardial catheters appear to offer a safe alternative to needle pericardiocentesis. Minimal sedation is required for placement, and they can be placed quickly. Their indwelling nature and use was not associated with a higher rate of arrhythmia compared to that of needle pericardiocentesis alone, and may be beneficial in the event that clinically significant PE recurs.